Reestructuración urbano regional y nuevos derroteros de la migración en la Región Centro de México. El caso de la ZMCM - Pérez Campuzano, Enrique (El Colegio de México A.C., 2006)
Migration is intimately related to regional factors. It is not only the wage differential between regions but a whole series of phenomena such as the supply of employment and housing, the search for better living conditions, urban growth, etc. that attract this population. From this perspective, this article seeks to analyze the migratory balance of the Metropolitan Zone of Mexico City (MZMC) within the restructuring process of the Central Region of the country.